RELATIONSHIP BETWEEN SERUM 25 OH VITAMIN D AND OTHER SERUM METABOLITE LEVELS OF HYPERTENSIVE AND NON HYPERTENSIVE PREGNANT WOMEN IN NIGERIA - Sanni, David Morakinyo; Osagie, Philip; Omotoyinbo, Oluwasegun Victor; Ekperigin, Mofoluso (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
Hypertension has been estimated to complicate 5 % of all pregnancies, with hypertensive disorders accounting for up to 40 000 maternal deaths annually. This study, therefore, seeks to investigate the effect hypertension has on some serum metabolites, namely; Serum 25-OH vitamin D (Vit. D), Alkaline phosphates (ALP), Inorganic phosphates (Pi), Calcium and Total protein level in hypertensive and non-hypertensive pregnant women at different gestation period/ trimesters. Vit. D was assayed by Elisa, while the other parameters were all assayed by the colorimetric method. Vit. D, Calcium, Pi and total protein had their highest values at non-hypertensive (control) conditions at all trimesters, while other hypertensive conditions from severe, mild to pre-hypertensive cases had steady increase in all the serum metabolites above mentioned except for Pi, which showed a sharp increase in its value between the mild and pre-hypertensive at all three stages studied: 0.09 ± 0.01 and 1.45± 0.12mmol/L at first trimester,0.087±0.01 and 1.23±0.12 mmol/L at second trimester, while at third trimester 0.07±0.01 and 1.03±0.12 mmol/L. However ALP showed different patterns with its highest mean enzyme activity observed for severe hypertensive cases;192.47±13.11U/L at first trimester, 197.32±18.11U/L in the second trimester and 212.47±21.71 U/L at third trimester. Therefore, all the serum metabolites understudied showed a significant relationship in the values obtained from the hypertensive and non-hypertensive patients considered and can serve as possible inference for early diagnosis of maternal and fetal complications in hypertension.